Commonly used methods to monitor driver’s drowsiness and fatigue with a focus on the interior camera - Kotas, Filip; Kotas, Filip; Leistner, Jan; Leistner, Jan (České vysoké učení technické v Praze, 2025)
Some of the main causes of road accidents nowadays are fatigue, drowsiness and driver inattention. In many cases, these accidents are fatal and can cause significant financial loss. Most of these accidents happen between midnight and 6am. One way to reduce the number of accidents caused by these causes is to use an interior camera. This camera can detect fatigue or drowsiness and alert the driver in time, and in the worst case, take over the car and stop safely at the side of the road. The aim of this article is to provide a comprehensive overview of the methods used to detect driver fatigue, drowsiness and inattention. A further objective is then to develop and process a survey that focuses on public awareness and opinions on the integration of interior cameras in vehicles across Europe.